Quantitative second harmonic generation imaging of leporine, canine, and porcine vocal fold collagen. (9th January 2019) - Devine, Erin E.; Liu, Yuming; Keikhosravi, Adib; Eliceiri, Kevin W.; Jiang, Jack J.
Abstract : Objectives/Hypothesis: Vocal fold collagen composition is an important determinant of material properties and mucosal wave propagation. Collagen alignment and straightness are quantitatively characterized by second harmonic generation (SHG) imaging. We examined leporine, canined and porcine vocal folds showing collagen composition variation that is species, location, and strain specific. Study Design: Animal model. Methods: Leporine (n = 5), canine (n = 5), and porcine (n = 5) larynges were harvested and fixed in situ. Samples were transversely sectioned, and SHG images were collected for two inferior–superior sections along five anterior–posterior locations. Additional porcine samples were fixed and imaged under tensile strain (0%, 5%, 10%, 15%, 20%, n = 5 per group). Two‐way repeated measures (RM) analysis of variance (ANOVA) tested for section and location differences in each species. Multiway RM‐ANOVA tested for section, location, and strain differences in porcine samples. Results: Alignment and straightness were higher inferiorly in the porcine ( P = .0047, P = .002) and canine ( P = .0011, P < .001) vocal folds, but not in leporine samples ( P = .67652, P = .4831). There were significant interactions between elongation and superior–inferior section for both alignment ( P = .0047) and straightness ( P = .0371). Conclusions: Our results correspond well to findings in the literature that the inferior vocal fold lip is stiffer in porcine and canine larynges. The absence of a collagen gradient in the leporine vocal fold is notable because rabbits are less vocal animals, indicating the collagen gradient may be a result of voice use and an important consideration in model selection when extracellular matrix is of interest. Strain results were also consistent with the role of collagen in strain stiffening behavior of vocal fold tissue. Level of Evidence: NA Laryngoscope, 129:2549–2556, 2019